The Role of Wishes in Tatar and English Linguistic Cultures - Nurgalieva, Leila A.; Saidasheva, Elmira A. (Journal of History Culture and Art Research, 2017)
Wishes are an important category of speech etiquette, whose significance in society culture and life is undeniable. The purpose of this article is to compare the main ways of wishes in two completely different linguistic cultures. The main research methods include comparative, definitional, component and contextual analysis and ethnic-linguistic-culturological one. In the process of the study, we came to the conclusion that one of the few units of speech etiquette can function in parallel with many other phenomena of speech etiquette, such as greeting, farewell, congratulation, condolence, gratitude, advice, etc. Despite the fact that wishes are a natural norm of communication, they have a huge force of influence on a person, as they are aimed on the creation of a good mood for an interlocutor. In Tatar and English, wishes have different forms of use, which characterizes them as the most common unit of speech etiquette. Wishes are chosen by a speaker with an emphasis on the generally accepted value system, on the idea of a value system of a listener, as well as his own ideas about what is good or bad, pleasant or unpleasant for an addressee. The materials of this article can be used in the practice of intercultural communication, in the translation process of teaching English to a Tatar language audience at higher education institutions and schools in order to develop intercultural communication among learners.